2015
DOI: 10.5897/jaerd2014.0635
|View full text |Cite
|
Sign up to set email alerts
|

New trends in rural community development practice in Africa: The case of Cameroons grassfield rural development project

Abstract: This paper examines a new trend in rural community development in Cameroon using the Grassfield Rural Development Project, to highlight the challenges of the participatory approach in an African context. There is an on-going debate about the future of the rural sector in developing countries, centred on implementation of participatory projects to alleviate poverty and deteriorating rural living conditions. Using data from project documents and evaluations, participant observation and interviews with key stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…asserted that barriers to development could be addressed by increasing domestic investments, transforming the trade and export structure, adopting technological advancements, and improving governance through the development of reforms, development strategies, and associated measures. Similarly, Amungwa (2015) suggested that Cameroon must develop sustainable approaches to support new trends in rural community development, such as investments in community infrastructure and social capital, and enhancing leadership and governance. His research supports our findings.…”
Section: The Benefits Of Globalizationmentioning
confidence: 99%
“…asserted that barriers to development could be addressed by increasing domestic investments, transforming the trade and export structure, adopting technological advancements, and improving governance through the development of reforms, development strategies, and associated measures. Similarly, Amungwa (2015) suggested that Cameroon must develop sustainable approaches to support new trends in rural community development, such as investments in community infrastructure and social capital, and enhancing leadership and governance. His research supports our findings.…”
Section: The Benefits Of Globalizationmentioning
confidence: 99%